2003
DOI: 10.1111/j.0006-341x.2003.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Generalized Concordance Correlation Coefficient through Variance Components

Abstract: The intraclass correlation coefficient (ICC) and the concordance correlation coefficient (CCC) are two of the most popular measures of agreement for variables measured on a continuous scale. Here, we demonstrate that ICC and CCC are the same measure of agreement estimated in two ways: by the variance components procedure and by the moment method. We propose estimating the CCC using variance components of a mixed effects model, instead of the common method of moments. With the variance components approach, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
224
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(238 citation statements)
references
References 17 publications
(47 reference statements)
4
224
0
3
Order By: Relevance
“…An acceptable agreement (CCC) 18 was observed between the microarray results and the qPCR results. There is a very small or no overlap between the list of validated genes identified in the current study and those reported previously.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…An acceptable agreement (CCC) 18 was observed between the microarray results and the qPCR results. There is a very small or no overlap between the list of validated genes identified in the current study and those reported previously.…”
mentioning
confidence: 70%
“…An agreement analysis between microarray and RT-PCR FC values was performed for each condition using the concordance correlation coefficient 18 (CCC), which yields values between 0 (independence) and 1 (perfect agreement). …”
Section: Concordance Between Microarray and Real-time Pcr Resultsmentioning
confidence: 99%
“…In order to assess the agreement between the assays, the first step is to model the data. The Linear mixed effects model is most commonly used in modeling the method comparison data [6][7][8][9][10][11][12][13][14][15]. Because of the flexibility in modeling of within subject dependence, linear mixed models are popular.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been proposed to model the method comparison data, among them the regression-based model doi: 10.7243/2053-7662-5-3 [6,9] and the standard mixed-effects models [24] are the most important. A standard mixed-effects model is used predominantly to model method comparison data [2,5,25,26,30]. The validation of the mixed-effects model highly depends on assumptions such as constant error variance (homoscedasticity) and normality of error terms.…”
Section: Introductionmentioning
confidence: 99%
“…The validation of the mixed-effects model highly depends on assumptions such as constant error variance (homoscedasticity) and normality of error terms. However, these assumptions are violated in practice [2,5,30]. Basically, the error variability may change with the magnitude of measurements.…”
Section: Introductionmentioning
confidence: 99%